The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/adma.201900880
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Selective Growth of Single‐Orientation Hexagonal Boron Nitride toward High‐Performance Atomically Thin Electric Barriers

Abstract: The family of 2D van der Waals (vdW) layered materials has attracted immense interest because of continuous discoveries of unique and intriguing physical phenomena in new members and stacked heterostructures. [1][2][3] However, a few issues regarding scalability and integration have to be resolved prior to practical applications. Among them is control of the crystal orientation of 2D vdW films, which is still elusive. One immediate benefit of single-orientation growth is the elimination of The ability to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…Figure 8b-d shows three experimental observations of hBN alignments on Cu{100} serial high-index surfaces reported in Li et al [4c] and Wang et al [10] All the three surfaces, Cu(102) (Figure 8b), Cu(103) (Figure 8c), and Cu(5 0 11) (Figure 8d), have step edges along the Cu<100> direction and the alignment of the ZZN edge of the hBN island along the step edge direction was confirmed by electron back scattering diffraction (EBSD) patterns and scanning electron microscope (SEM) images. Figure 8e-h shows four experimental observations of CVD grown hBN on Cu{110} serial high-index surfaces reported in Wang et al [7] and Wang et al [10] Figure 8e shows the alignment of hBN on a vicinal Cu(110) surface with Cu<211> step edges. The experimentally observed alignment of the ZZN edge along the step edge direction is in perfect agreement with our theoretical prediction.…”
Section: Summary and Comparison With Experimental Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Figure 8b-d shows three experimental observations of hBN alignments on Cu{100} serial high-index surfaces reported in Li et al [4c] and Wang et al [10] All the three surfaces, Cu(102) (Figure 8b), Cu(103) (Figure 8c), and Cu(5 0 11) (Figure 8d), have step edges along the Cu<100> direction and the alignment of the ZZN edge of the hBN island along the step edge direction was confirmed by electron back scattering diffraction (EBSD) patterns and scanning electron microscope (SEM) images. Figure 8e-h shows four experimental observations of CVD grown hBN on Cu{110} serial high-index surfaces reported in Wang et al [7] and Wang et al [10] Figure 8e shows the alignment of hBN on a vicinal Cu(110) surface with Cu<211> step edges. The experimentally observed alignment of the ZZN edge along the step edge direction is in perfect agreement with our theoretical prediction.…”
Section: Summary and Comparison With Experimental Resultsmentioning
confidence: 83%
“…Recently, a wide study of hBN growth on more than 100 different Cu facets was reported where unidirectional alignment of hBN islands was found on ≈30 different surfaces. [ 10 ] By a seeded growth technique, Wu et al. realized the production of more than 30 kinds of single crystalline high‐index Cu surfaces with a wafer size, and unidirectional alignments of both graphene and hBN islands on these high‐index surfaces were confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, the orientational uniformity of various 2D materials has been widely observed. As listed in Supplementary Table 4, epitaxial growth of well-aligned hBN islands have been observed on Cu(102), Cu(103), and vicinal Cu(110) surfaces 39,40 , where one of the three edges of the triangular hBN island is aligned along the step edge of the substrate. In addition, well-aligned WSe 2 islands were also observed on Al 2 O 3 (0001) surface with step edges 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, such a strategy has been used to grow wafer scale single-crystalline hBN on vicinal Cu(110) surface and Cu(111) surface with step egdes 8 , 9 , and centimeter scale single-crystalline MoS 2 on an Au(111) surface with aligned step edges 10 . DFT calculations in these studies have shown that the weak interaction between the bulk of the 2D material and the substrate and/or the strong interaction between the edge of 2D material and step edge of the substrate lead to the favorable alignment of the 2D islands along the step edges of the substrate 8 10 , 39 , 40 . Since high-index surfaces can be easily obtained by miscutting a single crystal, we believe that this could be a general strategy for the synthesis of various 2D materials in the future.…”
Section: Resultsmentioning
confidence: 99%